Analisis Pengelolaan Obat Sebagai Dasar Pengendalian Safety Stock pada Stagnant dan Stockout Obat - Fenty Ayu Rosmania; Stefanus Supriyanto (Universitas Airlangga, 2015)
ABSTRACT Stagnant and stockout of drug are the effects from the drug logistic management. In average of 52.43% stagnant and 19.08% stockout from 118 types of drugs in Primary Health Care from January to December 2014. This research aimed to analyzed drug management and the safety stock control of stagnant and stockout in Primary Health Care.This was quantitative research with descriptive method. Primary data was obtained by interview and observation. Secondary data obtained from LPLPO and drug planning data, it can be calculated for drug’s planning and safety stock required. Planning and procurement of drugs proposed for 2014 only has the suitability of 16,03% with the use of drugs by 2014. Receipt of drugs have a large enough discrepancy that is 76,93% of the demand for drugs in Primary Health Care. Distribution of drugs is less well with only 50% according to the procedure. Monitoring and control of the drugs have a quite well with 60% according to the procedure. While, no safety stock calculations at the Primary Health planning proposals in 2014. Process of drug management at Primary Health Care is not good enough. It needs improvements in systems planning, procurement, receipt, distribution, monitoring and control of drugs. Keywords: drug management, safety stock control, primary health care